A low dielectric loss aluminum nitride ceramic substrate and a method for manufacturing the same
By using specific composite additives and toughening agents in aluminum nitride ceramic substrates and optimizing the debinding and sintering processes, the problem of high dielectric loss in aluminum nitride ceramic substrates was solved, enabling the fabrication of aluminum nitride ceramic substrates with low dielectric loss and high bending strength, thereby improving signal transmission quality and production efficiency.
Patent Information
- Application Number
- CN202511203141.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-08-27
AI Technical Summary
Existing aluminum nitride ceramic substrates have high dielectric loss in high-frequency signal transmission, which leads to signal attenuation and reduced communication quality. Existing methods are difficult to effectively reduce dielectric loss and have high production costs or low efficiency.
A low dielectric loss aluminum nitride ceramic substrate was prepared by using a specific ratio of boron trioxide, calcium fluoride and lithium carbonate as composite additives, combined with alumina whiskers and silicon carbide whiskers as toughening agents, and using a vacuum and air debinding process to optimize the sintering process.
It significantly reduces the dielectric loss of aluminum nitride ceramic substrates, improves signal transmission quality and equipment performance, and also improves the bending strength and production efficiency of the substrates.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials technology, specifically to a low dielectric loss aluminum nitride ceramic substrate and its preparation method. Background Technology
[0002] Against the backdrop of rapid development in modern electronic technology, electronic products are constantly evolving towards miniaturization, lightweighting, high integration, and high performance. For integrated circuit substrates and packaging materials, their performance directly affects the overall performance of electronic devices. Aluminum nitride ceramics, with their unique comprehensive properties such as high thermal conductivity, low dielectric constant, excellent electrical insulation, a thermal expansion coefficient matching that of silicon, and non-toxicity, have become an ideal choice for high-density, high-power, and high-speed integrated circuit substrates and packaging, attracting widespread attention and research.
[0003] However, existing aluminum nitride ceramic substrates suffer from significant dielectric loss issues in practical applications. Dielectric loss refers to the energy loss caused by the conversion of electrical energy into heat energy due to internal polarization processes and charge movement within a dielectric material under the influence of an electric field. In high-frequency, high-speed signal transmission circuits, high dielectric loss leads to signal attenuation and distortion, severely impacting the performance and signal transmission quality of electronic devices. For example, in the power amplifier module of a 5G communication base station, if the aluminum nitride ceramic substrate used has high dielectric loss, a large amount of signal energy will be lost within the substrate during high-frequency signal processing, resulting in weakened output signal strength, waveform distortion, and severely reduced communication quality and efficiency.
[0004] Currently, the common methods to reduce the dielectric loss of aluminum nitride ceramics are: (1) From the perspective of raw materials, the use of high-purity, fine-grained aluminum nitride powder has a certain effect, but fine-grained powder has problems such as agglomeration during preparation and molding. (2) From the perspective of preparation process, traditional sintering methods such as hot pressing and isostatic pressing are costly and have low production efficiency, which cannot meet the growing market demand. Although aluminum nitride ceramic substrates prepared by tape casting can be used for large-scale production and have low production costs, their density is low, which will lead to an increase in dielectric loss. Therefore, it is necessary to develop a low dielectric loss aluminum nitride ceramic substrate to better meet the requirements of the electronics field for the dielectric loss of aluminum nitride ceramic substrates. Summary of the Invention
[0005] This invention proposes a low dielectric loss aluminum nitride ceramic substrate and its preparation method, which solves the problem of high dielectric loss in aluminum nitride ceramic substrates in related technologies.
[0006] The technical solution of the present invention is as follows:
[0007] This invention proposes a low dielectric loss aluminum nitride ceramic substrate, comprising the following raw materials in parts by weight: 80-90 parts aluminum nitride, 6-8 parts sintering aid, 3-5 parts toughening agent, 3-4 parts composite aid, 6-10 parts binder, 6-8 parts dispersant, and 60-70 parts solvent; wherein the composite aid includes boron trioxide, calcium fluoride, and lithium carbonate.
[0008] As a further technical solution, the mass ratio of boron trioxide, calcium fluoride and lithium carbonate is 1:1:3 to 5, for example, it can be 1:1:3, 1:1:4, 1:1:5, preferably 1:1:4.
[0009] In this invention, the specific ratio of boron trioxide, calcium fluoride, and lithium carbonate further improves the density of the ceramic, reduces internal porosity and defects, and also helps to further reduce dielectric loss. Limiting the mass ratio of boron trioxide, calcium fluoride, and lithium carbonate to 1:1:3~5 allows for a synergistic effect, further improving the density of the ceramic substrate, reducing internal porosity and defects, and lowering dielectric loss.
[0010] As a further technical solution, the dispersant can be any one or more conventional dispersants, preferably triethyl phosphate.
[0011] As a further technical solution, the toughening agent includes alumina whiskers and silicon carbide whiskers.
[0012] Both alumina and silicon carbide whiskers possess high strength and modulus. In aluminum nitride ceramic matrices, they can effectively bear external forces and transfer the load to the surrounding matrix, allowing the ceramic matrix to bear stress more evenly and avoiding stress concentration. Furthermore, the synergistic effect between whiskers and the matrix can be fully utilized to improve the overall flexural strength of the ceramic substrate. During the sintering process of aluminum nitride ceramics, the added alumina and silicon carbide whiskers can inhibit grain growth, and the refined grains increase the grain boundary area. Grain boundaries can hinder crack propagation, while also improving the strength and toughness of the ceramic matrix.
[0013] As a further technical solution, the mass ratio of the alumina whiskers to the silicon carbide whiskers is 1:2 to 4, for example, it can be 1:2, 1:3, or 1:4, preferably 1:3.
[0014] When alumina whiskers and silicon carbide whiskers are used in the proportions specified in this invention, a uniform microstructure can be formed in the ceramic substrate. The uniform distribution of the two types of whiskers in the matrix can more effectively hinder crack propagation and suppress grain growth. During sintering, an appropriate ratio of alumina whiskers and silicon carbide whiskers can form a stable network structure between ceramic grains, making the microstructure of the ceramic substrate more dense and uniform, and improving its overall performance.
[0015] As a further technical solution, the adhesive is polyvinyl butyral.
[0016] In the mixing process of aluminum nitride ceramic substrate raw materials, the binder imparts a certain degree of plasticity and viscosity to the green body. It binds the raw material particles, such as aluminum nitride, sintering aids, toughening agents, and composite additives, together. During the drying and handling of the green body, the binder maintains the integrity and strength of the green body, firmly bonding the raw material particles and preventing cracking and breakage during drying shrinkage. This ensures the green body can withstand the external forces during subsequent processing and handling. In the tape casting process, it imparts suitable rheological properties to the slurry, thus smoothly forming a uniform thin film green body on the tape casting machine.
[0017] As a further technical solution, the sintering aid includes one or two of calcium oxide and yttrium oxide.
[0018] As a further technical solution, the sintering aid is composed of calcium oxide and yttrium oxide in a mass ratio of 1:2.
[0019] Calcium oxide and yttrium oxide can make the microstructure of ceramics more uniform, reducing internal defects and porosity. Optimization of the microstructure helps reduce electron scattering and transitions within the ceramic, thereby reducing dielectric loss. The functional addition of calcium oxide and yttrium oxide can lower the sintering temperature of the ceramic green body and promote the densification of ceramic materials such as aluminum nitride during sintering, thus improving the flexural strength of the ceramic substrate.
[0020] As a further technical solution, the solvent includes one or more of isopropanol, ethyl acetate, and anhydrous ethanol.
[0021] The solvents selected in this invention can effectively dissolve binders and dispersants, allowing them to be evenly distributed in the raw material system. Moreover, they all have appropriate volatility, which facilitates the removal of solvents from the green body before drying and sintering, thus avoiding defects such as porosity and cracks caused by residual solvents inside the green body.
[0022] A method for preparing a low-dielectric-loss aluminum nitride ceramic substrate, comprising the following steps:
[0023] S1. Mix the raw materials to obtain a slurry;
[0024] S2. The slurry is cast and dried to obtain a blank material;
[0025] S3. The blank material is debonded and sintered to obtain a low dielectric loss aluminum nitride ceramic substrate.
[0026] As a further technical solution, in step S3, the glue removal is first performed by vacuum glue removal, and then by air glue removal.
[0027] In the desizing process, the extremely low oxygen content in the vacuum environment effectively inhibits incomplete combustion or carbonization of organic matter during volatilization, reducing residual carbon impurities. Following this, air desizing further oxidizes any remaining trace organic matter, decomposing it into harmless gases like carbon dioxide and water, thus reducing impurities and defects within the ceramic substrate and lowering dielectric loss. Furthermore, the reduced external pressure during vacuum desizing allows for more uniform volatilization of organic matter within the aluminum nitride ceramic substrate, preventing excessive internal stress caused by large local pressure differences and improving the bending strength of the aluminum nitride ceramic substrate. In contrast, the current process of nitrogen desizing followed by air desizing, while using nitrogen as an inert gas to some extent protects the ceramic substrate from oxidation, is less effective at decomposing and removing organic matter than vacuum desizing. This may leave behind more organic matter or carbon impurities, resulting in relatively higher dielectric loss. It also fails to effectively eliminate internal stress like vacuum desizing, leading to a decrease in the bending strength of the aluminum nitride ceramic substrate.
[0028] As a further technical solution, the process conditions for adhesive removal are as follows: under vacuum conditions, the temperature is raised to 350-450°C at a heating rate of 10-20°C / min for 4-6 hours, and then under air atmosphere, the temperature is raised to 500-550°C at a heating rate of 5-10°C / min for 4-6 hours. Preferably, under vacuum conditions, the temperature is raised to 350°C at a heating rate of 15°C / min for 4 hours, and then under air atmosphere, the temperature is raised to 500°C at a heating rate of 5°C / min for 6 hours.
[0029] In this invention, under vacuum conditions, the temperature is first raised to 350-450°C at a relatively rapid heating rate of 10-20°C / min. Vacuum debinding is then performed at a relatively low temperature, allowing the organic matter to begin volatilizing at a lower temperature. Rapid heating allows the binder, solvent, and other organic matter to quickly acquire sufficient energy to begin decomposition and volatilization. Simultaneously, the low temperature prevents excessively high temperatures from causing violent reactions and generating large amounts of gas, thus preventing excessive pressure differences within the ceramic and reducing defects such as pores and cracks. The reduction of these defects helps improve the density of the ceramic and increases the flexural strength of the aluminum nitride ceramic substrate. Debinding at 350-450°C for 4-6 hours provides sufficient time for the volatilization and decomposition of the organic matter, which is beneficial for improving the microstructural integrity of the ceramic, thereby increasing flexural strength.
[0030] Heating to 500-550℃ at a slow rate of 5-10℃ / min under air conditions allows for more uniform changes in the internal structure of the ceramic substrate during the heating process. Slow heating helps to gradually adjust and optimize the internal crystal structure of the ceramic, reducing internal stress caused by rapid temperature changes. Reduced internal stress effectively prevents the formation and propagation of microcracks, thereby improving the flexural strength of the ceramic substrate. Debinding the binder in an air atmosphere at 500-550℃ for 4-6 hours thoroughly oxidizes residual organic matter, converting it into gases such as carbon dioxide and water, further reducing impurities. This also helps stabilize the crystal structure of the ceramic, increasing its density and improving the flexural strength of the aluminum nitride ceramic substrate.
[0031] As a further technical solution, in step S3, the sintering temperature is 1450~1500℃ and the sintering time is 3~3.5h.
[0032] The working principle and beneficial effects of this invention are as follows:
[0033] In this invention, aluminum nitride possesses excellent electrical insulation properties and high thermal conductivity, making it a high-performance ceramic material. Its crystal structure is relatively stable, with a relatively ordered electron cloud distribution and low polarization under an electric field, providing a foundation for low dielectric loss in the ceramic substrate. The composite additive consists of boron trioxide, calcium fluoride, and lithium carbonate. Calcium fluoride promotes the decomposition of lithium carbonate to generate lithium oxide, lowering the liquid phase formation temperature and accelerating sintering. The addition of boron trioxide further lowers the sintering temperature, reduces internal porosity and defects, further reduces dielectric loss, improves signal transmission quality and reliability, lowers energy consumption costs, and thus enhances the overall performance of electronic devices. Detailed Implementation
[0034] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0035] In the following embodiments and comparative examples:
[0036] The particle size of aluminum nitride is 50 nm;
[0037] Alumina whiskers: diameter 0.5~1μm, length 10μm;
[0038] Silicon carbide whiskers: diameter 0.1~1μm, length 5~30μm;
[0039] The particle sizes of yttrium oxide, boron trioxide, calcium fluoride, and lithium carbonate are 10 μm, 300 nm, 13 μm, and 30 μm, respectively.
[0040] Example 1
[0041] A method for preparing a low dielectric loss aluminum nitride ceramic substrate includes the following steps:
[0042] S1. Mix 80 parts of aluminum nitride, 6 parts of sintering aid, 3 parts of alumina whiskers, 3 parts of composite aid, 6 parts of polyvinyl butyral (purchased from Hubei Darli Chemical Co., Ltd., product number Darl-1), 6 parts of triethyl phosphate, and 60 parts of isopropanol evenly to obtain a slurry; the composite aid consists of boron trioxide, calcium fluoride, and lithium carbonate in a mass ratio of 1:1:3; the sintering aid consists of calcium oxide (100nm) and yttrium oxide in a mass ratio of 1:2;
[0043] S2. The slurry is cast and dried to obtain the blank material;
[0044] S3. Under vacuum conditions, the blank is heated to 350°C at a heating rate of 10°C / min for 10 hours to remove the binder, and then sintered at 1450°C for 3.5 hours to obtain a low dielectric loss aluminum nitride ceramic substrate.
[0045] Example 2
[0046] A method for preparing a low dielectric loss aluminum nitride ceramic substrate includes the following steps:
[0047] S1. Mix 90 parts of aluminum nitride, 8 parts of sintering aid, 5 parts of alumina whiskers, 4 parts of composite aid, 10 parts of polyvinyl butyral (purchased from Hubei Darli Chemical Co., Ltd., product number Darl-1), 8 parts of triethyl phosphate, and 70 parts of isopropanol evenly to obtain a slurry; the composite aid consists of boron trioxide, calcium fluoride, and lithium carbonate in a mass ratio of 1:1:3; the sintering aid consists of calcium oxide (100nm) and yttrium oxide in a mass ratio of 1:2;
[0048] S2. The slurry is cast and dried to obtain the blank material;
[0049] S3. Under vacuum conditions, the blank is heated to 350°C at a heating rate of 10°C / min for 10 hours to remove the binder, and then sintered at 1500°C for 3 hours to obtain a low dielectric loss aluminum nitride ceramic substrate.
[0050] Example 3
[0051] Compared with Example 1, the only difference in this example is that the composite additive is composed of boron trioxide, calcium fluoride and lithium carbonate in a mass ratio of 1:1:5.
[0052] Example 4
[0053] Compared with Example 1, the only difference in this example is that the composite additive is composed of boron trioxide, calcium fluoride and lithium carbonate in a mass ratio of 1:1:4.
[0054] Example 5
[0055] Compared with Example 4, the only difference in this example is that the alumina whiskers are replaced with an equal amount of silicon carbide whiskers.
[0056] Example 6
[0057] Compared with Example 4, the only difference in this example is that the alumina whiskers are replaced with equal amounts of alumina whiskers and silicon carbide whiskers in a mass ratio of 1:3.
[0058] Example 7
[0059] Compared with Example 6, the only difference in this example is step S3. Step S3 in this example is: heating the blank to 500°C under air conditions at a heating rate of 5°C / min for 10 hours to remove the adhesive, thereby obtaining a low dielectric loss aluminum nitride ceramic substrate.
[0060] Example 8
[0061] Compared with Example 6, the only difference in this example is step S3. Step S3 in this example is: the blank is heated to 350°C under vacuum conditions at a heating rate of 10°C / min for 4 hours to remove the adhesive, and then heated to 500°C under air atmosphere at a heating rate of 5°C / min for 6 hours to remove the adhesive, thereby obtaining a low dielectric loss aluminum nitride ceramic substrate.
[0062] Example 9
[0063] Compared with Example 6, the only difference in this example is step S3. Step S3 in this example is: the blank is heated to 350°C under vacuum conditions at a heating rate of 15°C / min for 4 hours to remove the adhesive, and then heated to 500°C under air atmosphere at a heating rate of 5°C / min for 6 hours to remove the adhesive, thereby obtaining a low dielectric loss aluminum nitride ceramic substrate.
[0064] Example 10
[0065] Compared with Example 6, the only difference in this example is step S3. Step S3 in this example is: the blank is heated to 350°C under vacuum conditions at a heating rate of 20°C / min for 4 hours to remove the adhesive, and then heated to 500°C under air atmosphere at a heating rate of 5°C / min for 6 hours to remove the adhesive, thereby obtaining a low dielectric loss aluminum nitride ceramic substrate.
[0066] Example 11
[0067] Compared with Example 9, the only difference in this example is step S3. Step S3 in this example is: the blank is heated to 500°C in air at a heating rate of 5°C / min for 6 hours to remove the adhesive, and then heated to 350°C in vacuum at a heating rate of 15°C / min for 4 hours to remove the adhesive, thereby obtaining a low dielectric loss aluminum nitride ceramic substrate.
[0068] Comparative Example 1
[0069] Compared with Example 1, the only difference in this comparative example is that the composite additive is only boron trioxide.
[0070] Comparative Example 2
[0071] Compared with Example 1, the only difference in this comparative example is that the composite additive is only calcium fluoride.
[0072] Comparative Example 3
[0073] Compared with Example 1, the only difference in this comparative example is that the composite additive is only lithium carbonate.
[0074] Comparative Example 4
[0075] Compared with Example 1, the only difference in this comparative example is that the composite additive is calcium fluoride and lithium carbonate in a mass ratio of 1:3.
[0076] Comparative Example 5
[0077] Compared with Example 1, the only difference in this comparative example is that the composite additive is boron trioxide and calcium fluoride in a mass ratio of 1:1.
[0078] Comparative Example 6
[0079] Compared with Example 1, the only difference in this comparative example is that the composite additive is boron trioxide and lithium carbonate in a mass ratio of 1:3.
[0080] Comparative Example 7
[0081] Compared with Example 1, the only difference in this comparative example is that the composite additive is yttrium oxide, calcium fluoride and lithium carbonate in a mass ratio of 1:1:3.
[0082] Experimental Example 1
[0083] The dielectric loss of the aluminum nitride ceramic substrates in Examples 1-4 and Comparative Examples 1-7 was measured at room temperature using a broadband dielectric impedance meter. The test frequency was 1MHz, and the dielectric loss values were read. The measurement results are shown in Table 1 below.
[0084] Table 1. Dielectric loss measurement results
[0085]
[0086] As shown in Table 1, the dielectric loss of Examples 1-4 of the present invention is less than that of Comparative Examples 1-7, indicating that the composite additive composed of boron trioxide, calcium fluoride and lithium carbonate can reduce the dielectric loss of aluminum nitride ceramic substrate, improve signal transmission speed, reduce circuit power consumption and improve energy utilization efficiency.
[0087] Experiment Example 2
[0088] The aluminum nitride ceramic substrates prepared in Examples 4 to 11 were tested for bending strength according to the test method specified in GB / T6569-2006 "Test Method for Bending Strength of Fine Ceramics". The test method was three-point bending, and the results are shown in Table 2 below.
[0089] Table 2 Results of Bending Strength Test
[0090]
[0091] As shown in Table 2, the aluminum nitride ceramic substrate prepared by this invention has a bending strength of up to 484 MPa, exhibiting excellent mechanical properties.
[0092] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A low dielectric loss aluminum nitride ceramic substrate, characterized in that, The raw material comprises the following components in parts by weight: 80-90 parts aluminum nitride, 6-8 parts sintering aid, 3-5 parts toughening agent, 3-4 parts composite additive, 6-10 parts binder, 6-8 parts dispersant, and 60-70 parts solvent; wherein the composite additive includes boron trioxide, calcium fluoride, and lithium carbonate; The mass ratio of boron trioxide, calcium fluoride and lithium carbonate is 1:1:4; The method for preparing a low dielectric loss aluminum nitride ceramic substrate includes the following steps: S1. Mix the raw materials to obtain a slurry; S2. The slurry is cast and dried to obtain a blank material; S3. The blank material is debonded and sintered to obtain a low dielectric loss aluminum nitride ceramic substrate; The process conditions for removing the adhesive are as follows: under vacuum conditions, the temperature is raised to 350°C at a heating rate of 15°C / min for 4 hours, and then under air atmosphere, the temperature is raised to 500°C at a heating rate of 5°C / min for 6 hours.
2. The low dielectric loss aluminum nitride ceramic substrate according to claim 1, characterized in that, The toughening agent includes alumina whiskers and silicon carbide whiskers.
3. The low dielectric loss aluminum nitride ceramic substrate according to claim 2, characterized in that, The mass ratio of alumina whiskers to silicon carbide whiskers is 1:2~4.
4. The low dielectric loss aluminum nitride ceramic substrate according to claim 1, characterized in that, The adhesive is polyvinyl butyral.
5. The low dielectric loss aluminum nitride ceramic substrate according to claim 1, characterized in that, The sintering aids include one or both of calcium oxide and yttrium oxide.
6. The low dielectric loss aluminum nitride ceramic substrate according to claim 1, characterized in that, The solvent includes one or more of isopropanol, ethyl acetate, and anhydrous ethanol.
Citation Information
Patent Citations
Ternary solvent system aluminum nitride slurry formula for preparing high-heat conduction ceramic substrate
CN103880428A
Silicon carbide whisker toughened high-thermal-conductivity aluminum nitride ceramic substrate for high-power LEDs
CN106187261A
Slurry of high-performance aluminum nitride ceramic substrate and preparation method thereof
CN112374896A
Cited By
Aluminum nitride ceramic and preparation method thereof
CN122212771A